Sleep-related breathing disorders - Lin, Hsin-Ching (Advances in Oto-Rhino-Laryngology / series editor Patrick J. Bradley, 2017)
Many sleep-related breathing disorders (SRBD), especially obstructive sleep apnea, originate from upper airway abnormalities. The connection to cardio- and cerebrovascular comorbidities is significant and the impact on the general health of patients is noteworthy. In recent years, important advances have been made in the research, diagnosis, and treatment of SRBD due to a multidisciplinary approach. This volume incorporates contributions in which the efforts and expertise of more than thirty outstanding experts are shared. It provides a concise, practical, and comprehensive review of sleep medicine and will enable researchers and physicians to stay updated on the latest developments.